2020
DOI: 10.3389/fgene.2020.552971
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Novel BRCA1 and RAD50 Mutations Associated With Breast Cancer Predisposition in Tunisian Patients

Abstract: Background: Deleterious mutations on BRCA1/2 genes are known to confer high risk of developing breast and ovarian cancers. The identification of these mutations not only helped in selecting high risk individuals that need appropriate prevention approaches but also led to the development of the PARP-inhibitors targeted therapy. This study aims to assess the prevalence of the most frequent BRCA1 mutation in Tunisia, c.211dupA, and provide evidence of its common origin as well as its clinicopathological character… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

4
5

Authors

Journals

citations
Cited by 15 publications
(25 citation statements)
references
References 107 publications
3
22
0
Order By: Relevance
“…Nevertheless, it is already listed and classified as pathogenic in ClinVar and predicted to result in the substitution of Alanine to Glycine (p.Ala224Glyfs) which leads to BRCA1 protein truncation. Another new mutation was identified in BRCA1 gene, c.2418dupA, that was reported by our group for the first time in the Tunisian population and was not reported previously in other populations ( 51 ). c.3049G>T has been identified in one ovarian cancer patient.…”
Section: Discussionsupporting
confidence: 54%
“…Nevertheless, it is already listed and classified as pathogenic in ClinVar and predicted to result in the substitution of Alanine to Glycine (p.Ala224Glyfs) which leads to BRCA1 protein truncation. Another new mutation was identified in BRCA1 gene, c.2418dupA, that was reported by our group for the first time in the Tunisian population and was not reported previously in other populations ( 51 ). c.3049G>T has been identified in one ovarian cancer patient.…”
Section: Discussionsupporting
confidence: 54%
“…Nevertheless, it is already listed and classi ed as pathogenic in ClinVar and predicted to result in the substitution of Alanine to Glycine (p.Ala224Glyfs) which leads to BRCA1 protein truncation. Another new mutation was identi ed in BRCA1 gene, c.2418dupA, that was reported by our group for the rst time in the Tunisian population and was not reported previously in other populations [45]. c.3049G > T has been identi ed in one ovarian cancer patient.…”
Section: Discussionsupporting
confidence: 50%
“…This mutation has so far been reported only in hereditary breast/ovarian cancer families of Tunisian origin, particularly in the North-East region, suggesting a founder effect. In order to unravel the genetic speci cities of this mutation and to trace its origin a haplotype analysis has been conducted by our group on the North Eastern region [45]. Results have determined the founder haplotype segregating with this mutation and have revealed that it arose in the period of colonization approximately 130 years ago.…”
Section: Discussionmentioning
confidence: 99%
“…Hamdi et al, performed whole exome sequencing on seven Tunisian families with HBOC and identified four novel BC candidate genes ( MMS19 , DNAH3 , POLK and KATB6 ) [ 46 ]. Furthermore, other studies identified by exome sequencing, RCC1 and RAD50 as BC candidate susceptibility genes in Tunisian BRCA negative families [ 47 , 48 ].…”
Section: Discussionmentioning
confidence: 99%